Analysis of the Use of Sequence T2 SPACE Dark Fluid in MRI Brain Coronal Slice Examinations with Clinical Epilepsy at the National Brain Center Hospital - Legia Prananto; Khairil Anwar; Riska Sekar Febriani (Warmadewa University, 2023)
This research centers on Brain MRI examinations in patients with clinical epilepsy, featuring the incorporation of an additional T2 SPACE dark fluid sequence. Brain MRI examination with clinical epilepsy at National Brain Center Hospital is a frequent examination. Epilepsy is such a condition characterized by recurrent seizures caused by disturbances in the brain function. In relation to which, this research aims to analyze the use of dark fluid T2 SPACE sequences and analyze the results of MRI images on dark fluid T2 SPACE sequences for information on coronal MRI Brain anatomical images with clinical epilepsy at National Brain Center Hospital. As for the research design used was descriptive qualitative with a case study approach which was conducted starting from February up to May 2023 at National Brain Center Hospital using a Siemens Skyra MRI aircraft with a power of 3 Tesla. The populations of this research were the patients who had clinical Temporal Lobe Epilepsy (TLE) and the number of samples was 10 patients. The result of this study indicates that the use of the T2 SPACE dark fluid sequence produces more detailed images of the hippocampal structure in terms of slices. In addition, it provides good spatial resolution for assessing the hippocampal structure, allowing the visualization of abnormal signal intensities within the hippocampus, and facilitating the detection of hippocampal abnormalities. Therefore, it can be concluded that the use of T2 SPACE dark fluid sequence is very important and considerably quite informative in diagnosing epilepsy cases.